2022
DOI: 10.1177/00219983221088095
|View full text |Cite
|
Sign up to set email alerts
|

Strength and failure mechanism of single-lap magnesium-basalt fiber metal laminate adhesively bonded joints: Experimental and numerical assessments

Abstract: A quick literature search reveals the significant lack of data and information concerning magnesium-to-magnesium bonded joints as well as fiber-metal laminates (FMLs) made with magnesium alloys. Therefore, a systematic series of experimental and numerical investigations are carried out to assess the performance of single-lap joints mating FML adherends. The primary goal is to better understand the effects of geometrical and material parameters that influence the performance of magnesium-to-magnesium joints. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This greater bonding is attributed to the increased number of contact points and the mechanical interlocking or "hooking" effect created by the rough surface, which can provide a larger interfacial area and greater resistance to interfacial separation. Many theoretical and experimental studies demonstrated the positive correlation between surface roughness and bonding strength [6,7,25,49]. However, the relationship between surface roughness and adhesion strength is not always straightforward and also depends on the chemical nature of the metal surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This greater bonding is attributed to the increased number of contact points and the mechanical interlocking or "hooking" effect created by the rough surface, which can provide a larger interfacial area and greater resistance to interfacial separation. Many theoretical and experimental studies demonstrated the positive correlation between surface roughness and bonding strength [6,7,25,49]. However, the relationship between surface roughness and adhesion strength is not always straightforward and also depends on the chemical nature of the metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…Various surface treatment methods are available to enhance the adhesion at the metal-composite interface of FMLs. Mechanical methods, such as grit blasting and mechanical abrasion, can increase surface roughness and create a peak-and-valley surface structure, leading to improved initial adhesion and bonding strength [6,7]. Mohamad et al [8] explored the impact of aluminum surface roughness on the interfacial strength between metal and composites in FMLs, concluding that heightened surface roughness enhances bonding strength.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Various kinds of FMLs can be explored by combing different kinds of metals and fiber-reinforced composites, such as the common aramid fiber reinforced aluminum laminate (Arall), [2] glass fiber reinforced aluminum laminate (Glare), [3] carbon fiber reinforced aluminum laminate (Carall), [4] graphite or carbon fiber reinforced titanium laminate (TiGr), [5] and other new variants. [6][7][8][9][10] In addition to the numerous investigations on mechanical properties from the material point of view, recent investigations have also paid attention to the forming technique [11][12][13] and structural performance of FML, [14][15][16] which were aimed at extending the applications. By far, the most striking of FML is still its excellent damage tolerance, [17] which is the reason that FML can act as a promising candidate in aeronautics.…”
Section: Introductionmentioning
confidence: 99%